Institutional autonomy of jews in Poland after world war II on the example of the cooperative movement = Autonomia instytucjonalna Żydów w Polsce po drugiej wojnie światowej na przykładzie ruchu spółdzielczego - Rykała, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the origins, development and liquidation of the Jewish cooperative movement in Poland after the Second World War. It outlines the socio-political background, which contributed to the creation of a kind of national-cultural autonomy for the Jews, including one of its pillars - the cooperative movement.
Keywords: Jews; cooperatives; post-war period; the national-cultural autonomy; Żydzi; spółdzielnie; okres powojenny; autonomia narodowo-kulturalna